Investigating in the J-curve phenomenon in Tunisia- ARDL bound test approach - Shubaita, Elham; Mar’i, Muhammad; Seraj, Mehdi (Journal of Economics and Behavioral Studies, 2020)
This paper investigates the relationship between trade balance, real exchange rates, and incomes in Tunisia by adopting the autoregressive distributed model (ARDL) by using data over the period of 1980 to 2018. We also used the bound test cointegration between variables at a 10% significant level. Our findings show that the Tunisia economy does not match the Marshall-Lerner condition in the long run, that provides an accurate description of the particular situation for which a country currency devaluation or depreciation its currency under both fixed or floating regime is predicted to enhance the trade balance of a country, which means there is no j-curve phenomenon in the long run, which tries to differentiate between the change of short-run and long-run effects in the change of exchange rate on the trade balance. Our findings match the Marshall-Lerner condition in the short run and can confirm the existing j-curve in the case of Tunisia.